2015
DOI: 10.2215/cjn.01540214
|View full text |Cite
|
Sign up to set email alerts
|

Renal Arcuate Vein Microthrombi-Associated AKI

Abstract: Backgrounds and objectives This report describes six patients with AKI stages 2-3 (median admission creatinine level, 2.75 mg/dl [range, 1.58-5.44 mg/dl]), hematuria (five with hemoproteinuria), and unremarkable imaging with an unusual and unexplained histologic diagnosis on renal biopsy.Design, setting, participants, & measurements The patients were young adults who presented to two neighboring United Kingdom nephrology centers over a 40-month period (between July 2010 and November 2013). Four were male, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…In case series of 6 patients, all of them reported to have consumed alcohol and notably 4 out of 6 patients were either using NSAID or Acetaminophen for pain. Hematuria and proteinuria along with negative immunology screen was reported [11]. The other striking features are the presence of flank pain as a presenting complaint and demographically young patients [11][12][13].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In case series of 6 patients, all of them reported to have consumed alcohol and notably 4 out of 6 patients were either using NSAID or Acetaminophen for pain. Hematuria and proteinuria along with negative immunology screen was reported [11]. The other striking features are the presence of flank pain as a presenting complaint and demographically young patients [11][12][13].…”
Section: Discussionmentioning
confidence: 97%
“…Hematuria and proteinuria along with negative immunology screen was reported [11]. The other striking features are the presence of flank pain as a presenting complaint and demographically young patients [11][12][13]. Most often patients have had successful renal recovery with conservative management however there have been reports where temporary dialysis has been necessary [11,14].…”
Section: Discussionmentioning
confidence: 99%
“…An interesting study by Redfern et al . recently reported six young adults with AKI and thrombosis in the renal arcuate veins demonstrated by kidney biopsy [ 8 ]. However, in this study, the specific causality and the underlying pathophysiologic mechanisms remained elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, a recent study by Redfern et al . reported thrombosis in the renal arcuate veins (RAVT) demonstrated by kidney biopsy in young adult patients with AKI [ 8 ]. However, the precise incidence and underlying pathophysiologic mechanisms of RAVT leading to AKI in these patients remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Glucose-based solutions continue to be the most used in PD, although new, more biocompatible, less acidic solutions with lower GDP content have been developed over the years [ 54 ]. Although cell culture and animal studies have shown that the newer PD solutions achieve better biocompatibility than acidic glucose-based ones, this does not translate into clinical superiority [ 55 , 56 , 57 , 58 , 59 ]. Again, when one looks at the effect on biomarkers of angiogenesis and inflammation, VEGF and IL- 6 levels, there is no evidence of benefit [ 27 , 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%